Calcium carbonate crystallization in tailored constrained environments. Issue 31 (21st August 2015) - Beato, C.; Fernández, M. S.; Fermani, S.; Reggi, M.; Neira-Carrillo, A.; Rao, A.; Falini, G.; Arias, J. L.
<x xml:space="preserve">Abstract</x> This research shows that by tailoring the assembly of lecithin molecules it is possible to modulate the texture, polymorphism, size and shape of calcium carbonate crystals.